Human Resources Management Challenges and Solutions in Managing a Multi-Generational Workforce in the Digital Era - Galuh Boga Kuswara; Yulianah, Yulianah (Sean Institute, 2025)
This study aims to analyze the challenges faced by human resource (HRM) management in managing a multi-generational workforce in the digital age and identify strategic solutions that organizations can implement. The diversity of generations, consisting of Baby Boomers, Generation X, Generation Y (Millennials), and Generation Z, creates differences in work values, communication styles, technology use, and expectations regarding the work environment. The research method used was a qualitative approach, with a literature review of various journals, books, and recent research reports related to HRM management and multi-generational workforce dynamics. The results of this study indicate that managing a multi-generational workforce in the digital age is inseparable from a number of complex challenges. Intergenerational communication gaps, negative stereotypes, differences in work values, and limited digital skills are key obstacles frequently encountered in organizational environments. Furthermore, changes in the increasingly flexible work environment and diverse employee expectations add to the complexity faced by HRM management. However, the study also found that solutions such as open and empathetic communication, the use of multiple communication channels, ongoing training, the development of non-technical skills, and the implementation of HRIS technology can reduce gaps and increase work effectiveness. Efforts to build an inclusive work culture have been proven to strengthen cross-generational collaboration and create a more harmonious, productive, and adaptable work environment.